Права человека изложение фактов No. 9, Rev. 2 - United Nations Office of the High Commissioner for Human Rights (United Nations, 2013)
This series is produced by the Office of the United Nations High Commissioner for Human Rights (OHCHR) and deals with selected questions of human rights that are under active consideration or are of particular interest. The Fact Sheets are intended to assist an ever-wider audience in better understanding basic human rights, what the United Nations is doing to promote and protect them, and the international machinery available to help realize those rights.